Accuracy of bedside bidimensional transcranial ultrasound versus tomodensitometric measurement of the third ventricle. Issue 4 (26th January 2022) - Lasselin, Philippe; Grousson, Sebastien; Souza Netto, Edmundo Pereira; Balanca, Baptiste; Terrier, Anne; Dailler, Frederic; Haesbaert, Julie; Boublay, Nawele; Gory, Benjamin; Berhouma, Moncef; Lukaszewicz, Anne‐Claire
Abstract: Background and Purpose: To evaluate the accuracy of transcranial duplex sonography (TCS) for measuring the diameter of the third ventricle (DTV) and the brain midline shift (MLS), as compared to cerebral CT. Methods: Single‐center retrospective study including 177 patients admitted to the neurological intensive care unit (NICU). We studied the correlation between TCS and CT measurements of DTV and MLS using a Bland‐Altman analysis. The best threshold of DTV to diagnose acute hydrocephalus was evaluated with a receiver operating characteristic (ROC) analysis. Results: We analyzed 177 pairs of CT‐TCS measurements for DTV and 165 for MLS. The mean time interval between CT and TCS was 87 ± 73 minutes. Median DTV measurement on CT was 4 ± 3 mm, and 5 ± 3 mm by TCS. Median MLS on CT was 2 ± 3 mm, and 2 ± 4 mm by TCS. The Pearson correlation coefficient ( r 2 ) was .96 between TCS and CT measurements ( p < .001). The Bland‐Altman analysis found a proportional bias of 0.69 mm for the DTV with a limit of agreement ranging between –3.04 and 2.53 mm. For the MLS, the proportional bias was 0.23 mm with limits of agreements between –3.5 and 3.95. The area under the ROC curve was .97 for the detection of hydrocephalus by DTV on TCS, with a best threshold of 5.72 mm (Sensitivity [Se] = 92% Specificity [Sp] = 92.1%). Conclusions: TCS seems to be a reliable and accurate bedside technique for measuring both DTV and MLS, which might allow detection of acute hydrocephalus among NICU patients.